Increased platelet activation in early symptomatic versus asymptomatic carotid stenosis and relationship with microembolic status: Results from the Platelets And Carotid Stenosis (PACS) Study. - Coughlan, Tara; O'Neill, Desmond; Doherty, Colin; Colgan, Mary; Collins, Daniel (My University, 2013)
Abstract Background: Cerebral microembolic signals (MES) may predict increased stroke risk in carotid stenosis. However, the relationship between platelet counts or platelet activation status and MES in symptomatic versus asymptomatic carotid stenosis has not been comprehensively assessed. Setting: University teaching hospitals. Methods: This prospective, pilot observational study assessed platelet counts and platelet activation status, and the relationship between platelet activation and MES in asymptomatic versus early (≤4 weeks after TIA/stroke) and late phase (≥3 months) symptomatic moderate or severe (≥50%) carotid stenosis patients. Full blood count measurements were performed, and whole blood flow cytometry was used to quantify platelet surface activation marker expression (CD62P and CD63) and circulating leucocyte-platelet complexes. Bilateral simultaneous transcranial Doppler ultrasound monitoring of the middle cerebral arteries was performed for 1 hour to classify patients as MES-positive or MES-negative. Results: Data from 31 asymptomatic patients were compared with 46 symptomatic patients in the early phase, and 35 of these patients followed up to the late phase after symptom onset. The median platelet count (211 vs. 200 x 109/L; p=0.03) and the median % lymphocyte-platelet complexes were higher in early symptomatic than asymptomatic patients (2.8 vs. 2.4%, p=0.001). The % lymphocyte-platelet complexes was higher in early symptomatic than asymptomatic patients with ≥70% carotid stenosis (p=0.0005), and in symptomatic patients recruited within 7 days of symptom onset (p=0.028). Complete TCD data were available in 25 asymptomatic and 31 early phase symptomatic, and 27 late phase symptomatic patients. 12% of asymptomatic versus 32% of early phase symptomatic (p=0.02) and 19% of late phase symptomatic patients (p=0.2) were MES-positive. Early symptomatic MES-negative patients had ahigher % lymphocyte-platelet complexes than asymptomatic MES-negative patients (2.8 vs. 2.3%; p=0.0085). Discussion: Recently symptomatic carotid stenosis patients have higher platelet counts (potentially reflecting increased platelet production, mobilisation or reduced clearance) and platelet activation status than asymptomatic patients. MES were more frequently detected in early symptomatic than asymptomatic patients, but the differences between late symptomatic and asymptomatic groups were not significant. Increased lymphocyte-platelet complex formation in recently symptomatic vs. asymptomatic MES-negative patients indicates enhanced platelet activation in this early symptomatic subgroup. Platelet biomarkers, in combination with TCD, have the potential to aid risk-stratification in asymptomatic and symptomatic carotid stenosis patients.
PUBLISHED
Keywords: Microembolic Signals; Transcranial Doppler Ultrasound; Platelet Activation; Whole Blood Flow Cytometry; Carotid Stenosis; Ageing; Neuroscience